2019
DOI: 10.3310/hsdr07350
|View full text |Cite
|
Sign up to set email alerts
|

Intentional rounding in hospital wards to improve regular interaction and engagement between nurses and patients: a realist evaluation

Abstract: © Crown copyright 2013. Contains public sector information licensed under the Open Government Licence v3.0 © Queen’s Printer and Controller of HMSO 2019. This work was produced by Harris et al. under the terms of a commissioning contract issued by the Secretary of State for Health and Social Care. This issue may be freely reproduced for the purposes of private research and study and extracts (or indeed, the full report) may be included in professional journals provided that suitable ack… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 61 publications
(425 reference statements)
1
24
0
Order By: Relevance
“…Compassionate behaviors ( Straughair, 2019 ) are taught through pedagogy ( Hendry, 2019 ), learning objectives ( Lown, 2016 ; Sinclair et al, 2021 ; Wang et al, 2022 ) assessment ( Lown et al, 2016 ), and skills sets such as reflective listening ( Braillon and Taiebi, 2020 ; Su et al, 2021 ). Healthcare research has examined compassion from the perspective of: the predictors of compassion in healthcare professionals ( Fernando and Consedine, 2014 ; Bleiker et al, 2020 ; Pavlova et al, 2022 ); how care environment and organizational culture affect compassion ( Casagrande, 2016 ; Ali and Terry, 2017 ; Dev et al, 2019 ; Tehranineshat et al, 2019 ; Wiljer et al, 2019 ; Ali et al, 2022 ); compassion-maintaining strategies and interventions ( Blomberg et al, 2016 ; Terry et al, 2017 ; Flores and Brown, 2018 ; Baguley et al, 2020 ; Hopkins et al, 2021 ; Malenfant et al, 2022 ); compassionate leadership ( Dewar and Cook, 2014 ; de Zulueta, 2015 ; Lown et al, 2019 ; West et al, 2020 ); and regulation of compassionate caregiving ( Harris et al, 2019 ; Pedersen and Roelsgaard Obling, 2019 ). Culturally and critically informed perspectives of compassion highlight that different societies, professional groups, cultures, and generations hold different expectations and views about compassion ( Koopmann-Holm and Tsai, 2017 ; Sundus et al, 2020 ) which change over time ( Salvador Zaragozá et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Compassionate behaviors ( Straughair, 2019 ) are taught through pedagogy ( Hendry, 2019 ), learning objectives ( Lown, 2016 ; Sinclair et al, 2021 ; Wang et al, 2022 ) assessment ( Lown et al, 2016 ), and skills sets such as reflective listening ( Braillon and Taiebi, 2020 ; Su et al, 2021 ). Healthcare research has examined compassion from the perspective of: the predictors of compassion in healthcare professionals ( Fernando and Consedine, 2014 ; Bleiker et al, 2020 ; Pavlova et al, 2022 ); how care environment and organizational culture affect compassion ( Casagrande, 2016 ; Ali and Terry, 2017 ; Dev et al, 2019 ; Tehranineshat et al, 2019 ; Wiljer et al, 2019 ; Ali et al, 2022 ); compassion-maintaining strategies and interventions ( Blomberg et al, 2016 ; Terry et al, 2017 ; Flores and Brown, 2018 ; Baguley et al, 2020 ; Hopkins et al, 2021 ; Malenfant et al, 2022 ); compassionate leadership ( Dewar and Cook, 2014 ; de Zulueta, 2015 ; Lown et al, 2019 ; West et al, 2020 ); and regulation of compassionate caregiving ( Harris et al, 2019 ; Pedersen and Roelsgaard Obling, 2019 ). Culturally and critically informed perspectives of compassion highlight that different societies, professional groups, cultures, and generations hold different expectations and views about compassion ( Koopmann-Holm and Tsai, 2017 ; Sundus et al, 2020 ) which change over time ( Salvador Zaragozá et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Lastly, previous studies have reported frequent incorrect execution of the rounds, specifically with the final sentence “Is there anything else I can do for you? I’ll be back in …” [ 32 ]. If the healthcare professional does not return after the promised time, the patient may lose confidence in the healthcare professional and in the experimental intervention, thus triggering a sense of anxiety which leads to more frequent calls for assistance [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…. " [32]. If the healthcare professional does not return after the promised time, the patient may lose confidence in the healthcare professional and in the experimental intervention, thus triggering a sense of anxiety which leads to more frequent calls for assistance [31].…”
Section: Discussionmentioning
confidence: 99%
“…Nursing staff in our study reported that completion of documentation is considered as an indication that hourly rounding is being completed, while nurses in another study thought that documentation of hourly rounding is a waste of time and irrelevant (Francis et al, 2019). Documentation of hourly rounding can be seen by nursing staff as a tick exercise that affects the fidelity of the intervention (Harris et al, 2019). Also, it is used to make sure that care has been delivered as known in the inherited attitude in nursing practice, ‘if it is not documented, it is not done’ (Sims et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…According to nurses' perception in our study, hourly rounding effectively addressed patients' basic needs. (Harris et al, 2019) reported that nurses see hourly rounding as fundamental care and 'nothing new' and it is what nurses have always done with added documentation. This is important in the persuasion stage in identifying the early adopters or champions of the project to help facilitate the diffusion of the initiative to their peers (Fabry, 2015).…”
Section: Differences In Nurses' Perceptions According To Selected Var...mentioning
confidence: 99%